THE APPLICATION OF RECIPROCAL TEACHING METHOD FOR IMPROVING THE UNDERSTANDING OF MATHEMATICS CONCEPT OF 7TH GRADE STUDENTS SMP NEGERI 2 DEPOK. - Tatag Bagus Argikas; Nanang Khuzaini (Jurnal Mercumatika : Jurnal Penelitian Matematika dan Pendidikan Matematika, 2016)
This research aims to: (1) describe the implementation of learning mathematics with Reciprocal Teaching methods that is for improving the concept of learning understanding mathematic in class VIIA SMP Negeri 2 Depok. (2) Knowing the increased understanding of student learning in class VIIA SMP Negeri 2 Depok use Reciprocal Teaching methods. This research constitutes an action in class that is according along the teacher. The data of research was collated by sheet observations and each evaluation of cycles. That is done in two cycles. The first was retrieved the average value of student learning achievement of 70.96%. The second was retrieved achievement of 90.32%. Thus this learning model can increase student learning understanding. Key word: The understanding of Mathematical Concept, Reciprocal Teaching Method.